(untitled) (Research, Society and Development, 2020)
Objectives: to characterize the sociodemographic and health profile of telemonitored patients in a stomatherapy clinic and to describe the outcome of telemonitoring actions to these patients. Method: quantitative, descriptive and documentary study, carried out in a stomatherapy clinic in Rio de Janeiro, between April and October 2018. The collection was in the medical records of telemonitored patients, using an instrument containing sociodemographic and clinical variables. The data were processed using descriptive statistics. Results: 84 medical records were analyzed, most of them male (58.3%), aged between 52 and 73 years. 2.4% registered higher education, the majority were retired (37%) and residents of the city of Rio de Janeiro (70%). It was identified that 53.6% of the patients had wounds, 23.8% were incontinent and 22.6% had stomas. Regarding the outcome of telemonitoring, 28 (33.3%) patients had rescheduling of consultations and 19 (22.6%) obtained discharge. Conclusion: the knowledge of the profile of patients allows a more assertive care and help in care planning.